UJI ESCHERICHIA COLI DAN FLUORIDA AIR MINUM BUNGKUSAN PLASTIK PADA RUMAH MAKAN DI KECAMATAN RUMBAI PESISIR PEKANBARU - Agmalia, Dian; Hamidy, Rasoel; Anita, Sofia (Jurnal Kajian Lingkungan, 2013)
The requirements of drinking water contain no coliform and fluoride in about 1,5 ppm. Theaims of this research to to find out the concentration of escherichia coli anf fluoride wrappedusing plastic bags at restaurants in Rumbai Pesisir Pekanbaru. The method of this researchis an survey method. To analyse escherichia coli used Most Probable Number Method andfluoride used SPANDS Method. The results show that all sample bags (100%) taken werecontaminated by coliform and 60% contained escherichia coli. It was found that out of fivetested samples, two of them contained Fluoride more than maximum threshold requirement ofthe drinking water quality when referred to the Health Minister Regulation Number492/Menkes/PER/IV/2010.